REMEDIATION OF A RAILWAY EMBANKMENT USING GEOCELLS AND DEEP SOIL MIXING - A NUMERICAL ANALYSIS - Jan Štefaňák; Josef Vašina (Acta Polytechnica CTU Proceedings, 2022)
Progressive settlement of the embankment under the railway track near Žďár nad Sázavou, the Czech Republic, has been observed for many years. Immediate improvement was needed to secure the safety of the traffic and to increase the travel speed of the track. The reconstruction work consisted of deep soil mixing. Also, a load spreading geocell reinforced mattress was designed. The evaluation of the proposed solution by means of numerical modelling and associated laboratory testing is described in the paper.